Enhancement of aqueous stability and fluorescence brightness of indocyanine green using small calix[4]arene micelles for near-infrared fluorescence imaging12. Issue 4 (26th February 2016) - Jin, Takashi; Tsuboi, Setsuko; Komatsuzaki, Akihito; Imamura, Yukio; Muranaka, Yoshinori; Sakata, Takao; Yasuda, Hidehiro
Abstract : Incorporation of ICG into calix[4]arene micelles improves its aqueous stability and fluorescence brightness. Abstract : Indocyanine green (ICG) is the only near-infrared (NIR) fluorescent dye which is approved for medical applications. However, ICG has several drawbacks such as aqueous instability, photodegradation, and low fluorescence quantum yield (2.5% in water), which lead to the limitation on the use of ICG for in vitro and in vivo NIR fluorescence imaging. Free ICG rapidly aggregates in physiological buffer solutions, and its fluorescence diminishes within several days. The objective of this work is to provide an easy method for the enhancement of the stability and fluorescence brightness of ICG in aqueous solutions for NIR fluorescence imaging. Herein, we report that the incorporation of ICG into small calix[4]arene (S4-6 ) micelles (<5 nm in diameter) significantly improves the aqueous stability and fluorescence brightness of ICG. The fluorescence quantum yields of ICG-calix[4]arene micelles are increased up to ∼6% in aqueous solutions. Using the ICG-calix[4]arene micelles, we achieved non-invasive NIR fluorescence imaging of the liver and lymph system in mice. Furthermore, we achieved NIR fluorescence imaging of nude mice bearing human breast tumors using an ICG conjugated antibody which is incorporated into the calix[4]arene micelles. Preparation of the calix[4]arene micelles including ICG is very easy and the micelle system does not show significant cytotoxicity. The ICG-calix[4]arene micelle system acts as a highly stable and bright probe for in vitro and in vivo NIR fluorescence imaging.